1965
DOI: 10.1029/jz070i005p01231
|View full text |Cite
|
Sign up to set email alerts
|

Tail of the magnetosphere

Abstract: The Chapman and Ferraro [e.g., Beard, 1960] model of the magnetosphere is entirely dissipationless and, as a consequence, contains no tangential stress at the magnetosphere boundary. It has been suggested that either viscous interaction [Axford and Hines, 1961; Piddington, 1963] or reconnection of field lines [Dungey, 1961; Levy, Petschek, and Siscoe, 1963] can give rise to tangential stresses which produce internal convection within the magnetosphere. A number of auroral and ionospheric observations appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
69
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(74 citation statements)
references
References 16 publications
5
69
0
Order By: Relevance
“…in agreement with the theoretical picture drawn by Axford et al (1965). A tubular "bundling" of the lines of force drawn back into the tail from each of the magnetic poles would result in a thickening of the sheet toward the flanks also.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…in agreement with the theoretical picture drawn by Axford et al (1965). A tubular "bundling" of the lines of force drawn back into the tail from each of the magnetic poles would result in a thickening of the sheet toward the flanks also.…”
supporting
confidence: 78%
“…Particle measurements by Anderson (1965a, b), Anderson et al (1965), Freeman (1964), Gringauz et al (1960) , McDiarmid and Burrows (1965), Montgomery et al (1965) and Singer et al (1965) have found enhanced particle fluxes on the night side of the Earth. Certain of these are probably related to the neutral sheet ' (Axford et al , 1965). Particularly pertinent in this respect are measurements by Frank (1965) with the Explorer 14 satellite which revealed the formation Of an ''electron tail" of the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This model (Williams and Mead, 1965), employing a current sheet and consequent tail configuration similar to that observed (Ness, 1965) and suggested (Piddington, 1960;Axford et al, 1965;Dessler and Juday, 1965), was quite successful in explaining quiet time electron distributions a s observed at 1100 km and thus demonstrated the strong influence of the geomagnetic tail in determining quiet time trapped particle spatial distributions. In this present study current sheet parameters were held fixed a t an inner edge of 8RE and an outer edge of 200 RE for all available cases.…”
mentioning
confidence: 94%
“…Furthermore, recent measurements (Bame et al, 1966) indicate a sheet thickness of -6 RE a t 1 7 RE and an extension of the sheet across the magnetospheric tail. Thus a current system in the tail region having spatial characteristics similar to that discussed by Axford et al, 1965) is indicated. * Nevertheless, in three cases, the A c motion is in good agreement with the predictions of the presently used simplified tail configuration employing simultaneously observed tail field strengths.…”
mentioning
confidence: 99%
“…Numerical simulations are also in vogue at this time. Early studies of the aerodynamic and MHD interactions of the solar wind with the geomagnetic field were presented by Levy et al (1964), Axford et al (1965) and Siscoe (1966). An interesting utilization of those studies was the Avco-Everett Research Laboratories (AERL) 1963 Christmas card portrayal (see Figure 2) since the work had been supported by that private sector firm.…”
Section: Introductionmentioning
confidence: 99%